Decision support system for comparative radiography - Bermejo, Enrique; Mesejo, Pablo; Ibanez, Oscar (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2023)
We introduce a hierarchical decision support system for comparative radiography. This system aims to support the forensic expert in the final decision making by considering multiple sources of information and uncertainty.
Keywords: comparative radiography; decision support; artificial intelligence